China's troubled bank loans : workout and prevention - Lou, Jianbo (London ; Boston, MA : Kluwer Academic Publishers, 2001)
The purpose of this book is to examine the significant and increasing problem of state bank non-performing loans (NPLs) in China, which have undermined the stability of the banking system and the efficient operation of markets. The accumulation of NPLs in China has been caused by the dominant role of State banks in China's financial markets, weak internal controls within State banks, policy loans to state owned enterprises, unnecessary administrative controls on banks' lending activities, and inappropriate banking regulation and supervision.
Includes bibliographical references (p. [351]-404) and index.
oif 27/08/15, ijb 07/03/2019
Loan
Keywords: Banks and banking; Bank loans